Pedriatric Population in Disaster: How Should We Care for Them? - Siregar, Nabilah (IJNP (Indonesian Journal of Nursing Practices), 2018)
AbstractBackground: Disaster might cause many impacts for vulnerable people, especially children (pediatric population).Objective: This paper aims to explain how should nurse do in caring for children in disaster management. Method: This review is conducted by searching many literatures from Science direct, ProQuest, PubMed, and google scholar about children and care for pediatric population. Result: Management for children in disaster should consider to many important things, such as: physical condition, psychology, development and behavior. Health practitioner include nurse should care for and involve families, consider to physical and psychological need and protect children from exploitation or any harms to prevent Post Traumatic Distress Syndrome (PTSD) in disaster management. Nurse should pay more attention for children as a unique vulnerable population by considering all aspects of pediatric and involve their families in disaster management.